OX40L gene polymorphism and breast cancer in Iranian population - Vakil Monfared, R.; Mashayekhi, F. (Experimental Oncology, 2018)
Background and Aim: The immune system plays an important role in the breast cancer development. OX40L (also known as TNFSF4), a membrane protein, which is a member of the tumor necrosis factor super family binds to its receptor OX40 and this co-stimulation has a crucial role in T cell proliferation, survival and cytokine release. Previous studies have shown that OX40L is associated with cancer. Due to the importance of the T cells in antitumor activities of OX40L we studied the association of rs3850641 (A→G) polymorphism of OX40L gene with the breast cancer. Materials and Methods: The study included 123 women with breast cancer and 126 healthy volunteers with no signs of cancer. Genomic DNA was extracted from blood leucocytes. Genotype and allele frequencies were determined in patients and control cases with the method of polymerase chain reaction-restriction fragment length polymorphism and the statistical analysis was performed by Med Calc. Results: The prevalence of genotype frequencies of AA/AG/GG were 60.9%, 30.08% and 8.9% in patients with breast cancer cases and 74.6%, 18.25% and 7.14% in healthy volunteers while the A and G allelic frequency was 76.01 and 23.98% in patients and 83.73 and 16.26% in healthy controls, respectively. Statistical analysis has shown signiﬁcant difference from the comparison of genotype (p = 0.03). Conclusion: It is concluded that the rs3850641 SNP is significantly associated with the breast cancer susceptibility in Iranian population. However, further studies in larger populations including other genetic and environmental factors are required to achieve conclusion. Key Words: OX40L, gene polymorphism, breast cancer, PCR-RFLP.